2007
DOI: 10.1093/rheumatology/kel161
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel autoantibody reactive with 155 and 140 kDa nuclear proteins in patients with dermatomyositis: an association with malignancy

Abstract: This novel MSA is associated with cancer-associated DM and may serve as a diagnostic serological marker for this specific subset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
211
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(236 citation statements)
references
References 16 publications
17
211
0
8
Order By: Relevance
“…A variety of serum autoantibodies are specifically detected in patients with PM/DM, including antibodies reactive with aminoacyl-transfer RNA synthetase (aaRS) (5), signal recognition particle (SRP) (6), Mi-2 (7), and p155 (8,9). These autoantibodies are associated with distinct clinical subsets of PM/DM.…”
mentioning
confidence: 99%
“…A variety of serum autoantibodies are specifically detected in patients with PM/DM, including antibodies reactive with aminoacyl-transfer RNA synthetase (aaRS) (5), signal recognition particle (SRP) (6), Mi-2 (7), and p155 (8,9). These autoantibodies are associated with distinct clinical subsets of PM/DM.…”
mentioning
confidence: 99%
“…It was described first by Targoff et al (Targoff et al, 2006b). The clinical manifestations of this reactivity involve high prevalences in dermatomyositis, as reported by Targoff et al, but with a high specificity the occurrence of this MSA correlates with a risk of malignancies as (Kaji et al, 2007). This observation was statistically underlined when Selva O´Canaghan et al performed a meta analysis for anti TIF 1 gamma antibodies and predictive values for malignancies (Selva-O'Callaghan et al, 2010) and found that anti p155/TIF1 y antibodies have a 70 % sensitivity and a 90 % specificity to detect occult malignancies in DM.…”
Section: Tif1 Gammamentioning
confidence: 67%
“…It was demonstrated that antigenic myositis-specific autoantigens are expressed in both tumor cells and myoblasts, and then myositis-specific autoantigen is expressed in an initial tumor leading to the generation of both specific T and B cells targeting those antigens, and subsequently stimulate immune responses previously generated in the anti-tumor response. [12][13][14][15] These may explain the mechanism of the coexistence of DM and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…16 Thus, the determination of clinical and laboratory signs for association with malignancy are of great importance for the disease prognosis. In some studies, relatively high proportions of anti-155/140 antibodies were detected in cancer-associated DM patients, and these have an excellent positive predictive value 12,13,17 Therefore, introduction of a commercial kit for this antibody to be applied in clinical screening may be beneficial. It was also shown that anti-Jo-1 antibody and cancer-associated DM, or interstitial lung disease and cancerassociated DM appear mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%